Role of Ramayana in Transformation of the Personal and Professional Life of Indians: An Empirical Investigation Based on Age and Regions - Pallathadka, Harikumar; Pallathadka, Laxmi Kirana; Pushparaj; Devi, Telem Kamlabati (Integrated Journal for Research in Arts and Humanities, 2022)
Ramayana is one of the greatest and holiest Sanskrit epics and one of the first written pieces of literature in the context of India. In the past few centuries, several authors have been exploring different dimensions of the epic Ramayana, which range from spirituality, philosophy, economics, politics, language, culture, poetry, literature, and technology. However, management does not seem to be popular in terms of subject analysis from Ramayana, even though Valmik Ramayana offers examples of several managers. Thus, several studies have been done to fill the gap in the literature by simply exploring the relevance of Ramayana for the growth and development of contemporary managers. These papers explore dharmic management, work motivation, vigilance, principles for control from Ramayana that offers lessons for improving managerial efficiency. The prospects to explore Ramayana in the other management domains like people management, and strategy management, may also be considered in the future.